Serum Concentration of Interleukin-6 Is Increased Both in Active and Remission Stages of Pemphigus Vulgaris - Joanna Narbutt; Jolanta Lukamowicz; Jarosław Bogaczewicz; Anna Sysa-Jedrzejowska; Jolanta Dorota Torzecka; Aleksandra Lesiak (Mediators of Inflammation)
As most studies on pemphigus vulgaris (PV) pathogenesis concern its active stage, we aimed to evaluate the serum concentration of TNF-α, IL-1, and IL-6 in PV patients in clinical remission. The study group consisted of sera from 19 PV patients in active stage and from 24 patients in clinical remission. 19 sera taken from healthy subjects served as the controls. Serum IL-6 concentrations in PV active and PV remission group were significantly higher when compared to the controls (P<.05). In patients in active stage of PV, a significant correlation between serum IL-1 and IL-6 concentrations was found (rP=0.46;P<.05). We also found a negative correlation between TNF-α level and pemphigus antibodies titer in the patients from the remission group (rS=−0.47303;P<.02). Our data suggest that IL-6 and TNF-α may be involved in maintaining immunological disturbances in remission stage of PV.